Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/gepi.22454
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐environment interaction in type 2 diabetes in Korean cohorts: Interaction of a type 2 diabetes polygenic risk score with triglyceride and cholesterol on fasting glucose levels

Abstract: Type 2 diabetes (T2D) is caused by genetic and environmental factors as well as gene‐environment interactions. However, these interactions have not been systematically investigated. We analyzed these interactions for T2D and fasting glucose levels in three Korean cohorts, HEXA, KARE, and CAVAS, using the baseline data with a multiple regression model. Two polygenic risk scores for T2D (PRST2D) and fasting glucose (PRSFG) were calculated using 488 and 82 single nucleotide polymorphisms (SNP) for T2D and fasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Our findings also provide insights into the role of lipoprotein classes in T2D etiology. For example, TG levels have been described to be positively associated with T2D 41 and are known to positively correlate with glucose levels, a relationship that may be exacerbated in individuals with high polygenic risk scores for T2D 49 . TG levels, which we found to be causally affected by T2D liability and for some of the related percentages significant in our interaction QTL analysis, may therefore contribute to increased glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also provide insights into the role of lipoprotein classes in T2D etiology. For example, TG levels have been described to be positively associated with T2D 41 and are known to positively correlate with glucose levels, a relationship that may be exacerbated in individuals with high polygenic risk scores for T2D 49 . TG levels, which we found to be causally affected by T2D liability and for some of the related percentages significant in our interaction QTL analysis, may therefore contribute to increased glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, López-Portillo et al demonstrated that fasting glucose levels were higher in non-diabetic individuals with increased genetic risk for T2D and higher consumption of sugary beverages, compared to those with lower genetic risk scores and reduced intakes of the latter 29 . Biochemical interactions have also been studied, where PRS for T2D have been found to significantly interact with triglyceride and cholesterol levels in the subsequent formation of fasting glucose levels 30 . Merino et al showed the dominating effect of unhealthy diet in increasing T2D risk even by 30%, again irrespective of genetic risk 31 .…”
Section: Prs Interactions With Lifestyle Determinantsmentioning
confidence: 99%